Effect of Tank-Mixing Glyphosate, Dicamba, and Graminicides on Grass Weed Control in Roundup Ready 2 Xtend Soybeans - R. Liu; I. Effertz; T. Lambert; A. Jhala; V. Kumar (Kansas Agricultural Experiment Station Research Reports, 2021)
The adoption of Roundup Ready 2 Xtendsoybean allows growers to use dicamba (Xtendimax or Engenia) in mixtures with glyphosate (Roundup PowerMax) or graminicides (Select Max or Assure II) for broad spectrum weed control. However, anecdotal evidence suggests that Xtendimax may cause antagonism when applied with Select Max and/or Assure II herbicides. The main objective of this study was to determine the effectiveness of Roundup PowerMax, Select Max, and/or Assure II alone or in tank-mixtures with Xtendimax for grass weed control in Xtendsoybean. Field studies were conducted in 2020 at the Kansas State University Agricultural Research Center (KSU-ARC) near Hays, KS, and at the University of Nebraska, Lincoln, NE (UNL). The dominant grass species at the KSU-ARC site were southwest cupgrass and green foxtail. The dominant grass weed species at the UNL site were giant foxtail, hairy cupgrass, and fall panicum. Treatments, including Select Max, Assure II, and Roundup PowerMax applied as early post-emergence (EPOST; V3-V4 soybean growth stage) alone, or in combination with Xtendimax were tested (see Table 1 for details). Results from the KSU-ARC site indicated that Roundup PowerMax applied alone and in sequential treatments at 5 days prior to or after the application of Xtendimax provided ≥ 85% control of both grass species, whereas the rest of the treatments provided ≤ 71% control. The highest soybean grain yield (13 to 17 bu/a) was observed with Roundup PowerMax alone or in tank-mixtures with Select Max, Assure II and/or Xtendimax. In contrast, tank-mixing Xtendimax to Select Max or Assure II, or Xtendimax applied 5 days prior to the application of Select Max or Assure II, reduced giant foxtail (64 to 82%), and hairy cupgrass (71 to 82%) control at the UNL site. The addition of Roundup PowerMax to tank-mixtures of Xtendimax with Select Max or Assure II restored the efficacy of both Select Max and Assure II on all three grass species. Soybean grain yield (64 to 77 bu/a) did not differ for the majority of treatments at UNL site. These results suggest that addition of Xtendimax with Select Max or Assure II can potentially compromise the efficacy of graminicides, and Roundup PowerMax should be added in these mixtures to optimize grass control in Roundup Ready 2 Xtendsoybean.
Keywords: Assure II; dicamba; glyphosate; graminicide; herbicide interaction; Roundup Ready 2 Xtend soybeans